2021
DOI: 10.3390/antiox10040560
|View full text |Cite
|
Sign up to set email alerts
|

Interplay among Antioxidant System, Hormone Profile and Carbohydrate Metabolism during Bud Dormancy Breaking in a High-Chill Peach Variety

Abstract: (1) Background: Prunus species have the ability to suspend (induce dormancy) and restart growth, in an intricate process in which environmental and physiological factors interact. (2) Methods: In this work, we studied the evolution of sugars, antioxidant metabolism, and abscisic acid (ABA) and gibberellins (GAs) levels during bud dormancy evolution in a high-chill peach variety, grown for two seasons in two different geographical areas with different annual media temperature, a cold (CA) and a temperate area (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
(122 reference statements)
2
15
0
Order By: Relevance
“…For instance, in the low-chill peach cultivar “Okinawa,” the glucose level remains unchanged during the endodormancy and increases significantly during the ecodormancy stage ( Hernández et al, 2021b ). In contrast, in a high-chill peach cultivar., “Yumyeong,” glucose level declines throughout the endodormancy and increases in ecodormancy, and similar accumulation pattern was observed in the fructose content ( Hernández et al, 2021a ). It has been also reported that starch accumulates gradually during endodormancy and hydrolyzes into soluble sugars by amylase at dormancy release and bud break ( Gholizadeh et al, 2017 ; Kaufman and Blanke, 2017 ), whereas others show starch degradation throughout the dormancy cycle ( Zhang et al, 2018 ).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…For instance, in the low-chill peach cultivar “Okinawa,” the glucose level remains unchanged during the endodormancy and increases significantly during the ecodormancy stage ( Hernández et al, 2021b ). In contrast, in a high-chill peach cultivar., “Yumyeong,” glucose level declines throughout the endodormancy and increases in ecodormancy, and similar accumulation pattern was observed in the fructose content ( Hernández et al, 2021a ). It has been also reported that starch accumulates gradually during endodormancy and hydrolyzes into soluble sugars by amylase at dormancy release and bud break ( Gholizadeh et al, 2017 ; Kaufman and Blanke, 2017 ), whereas others show starch degradation throughout the dormancy cycle ( Zhang et al, 2018 ).…”
Section: Introductionsupporting
confidence: 53%
“…Bud cells have the capacity to produce and scavenge different forms of ROS at various levels, as a result of a balance between their formation and detoxification, with a tight link to dormancy maintenance and release ( Beauvieux et al, 2018 ; Hernández et al, 2021a ). The ROS generation, including H 2 O 2 , may work as major signaling molecules for the endodormancy release ( Pérez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the role of NADPH oxidase during dormancy transition in deciduous fruit trees. Both non-enzymatic antioxidants such as glutathione and enzymatic antioxidants such as superoxide dismutase, catalase, glutathione peroxidase and glutathione reductase play crucial roles in maintaining optimum levels of ROS during dormancy [25,[36][37][38][39][40]. Comparisons of several transcriptomic studies showed induction of the same set of genes after exposure to chilling, HC or H 2 O 2 .…”
Section: Introductionmentioning
confidence: 98%
“…Sugars also provide the carbon skeleton for metabolites necessary for bud differentiation, growth and development. Changes in sugar levels during dormancy and dormancy release have been demonstrated in several woody perennials including apple [21], apricot [22], grape [23], Japanese pear [24], peach [25], and sweet cherry [26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that ROS can stimulate gibberellins (GA) biosynthesis [7,8]. Thus, ROS can favour the decline in the ABA/GAs ratio during seed germination [6,7] in a similar fashion to that reported in the dormancy release in floral buds [9,10].…”
mentioning
confidence: 72%